Ten-year risk assessment for type 2 diabetes mellitus using the Finnish Diabetes Risk Score in family medicine - Suzana Savić; Saša Stanivuković; Biljana Lakić (Medicinski glasnik, 2020)
Aim: To assess ten-year risk of diabetes mellitus type 2 (T2DM) using the Finnish Diabetes Risk Score (FINDRISC) in respondents over 18, in Primary Health Centre in Banja Luka. Methods: A prospective study was conducted using data from a population with undiagnosed T2DM in Primary Health Centre in Banja Luka. Eligible respondents were those aged 18 to 70 years. Sociodemographic, behavioural and anthropometric variables were those related to the risk models evaluated by FINDRISC. Results: Data were collected from 520 individuals, 58.8% female and 41.2% male (p=0.005). A very high risk of developing T2DM in the next ten years was found in 5.6% females and 3.7% males. A high risk was found in 12.4% females and 15.9% males, 34.2% respondents ? 65 years, 28.8% with body mass index >30 kg/m 2 , 26.6% who were not practicing physical activity (p=0.000), 24.0% who took antihypertensive drugs, 42.3% who were diagnosed with impaired glycaemia, 30.4% and 22.9% respondents whose parents and distant relatives, respectively, had T2DM. A moderate risk occurred in 31.4% females with waist circumference >88 cm. Half (50%) males with waist circumference >102 cm and 33.2% respondents who were not eating fruits and vegetables every day had a slightly increased risk of developing T2DM (p<0.05). Conclusion: The FINDRISC may be used as a tool which would help general practitioners in everyday work, to detect patients with T2DM risk factors and to encourage them to change life style towards healthy habits.
Keywords: Diabetes Registry; life style changes; primary health centre Banja Luka; prospective study